Niobium: The Focus on Catalytic Application in the Conversion of Biomass and Biomass Derivatives - Oliveira, Luiz; Pereira, Márcio; Pacheli Heitman, Ana; Filho, José; Oliveira, Cinthia; Ziolek, Maria (Molecules (Basel, Switzerland), 2023)
The world scenario regarding consumption and demand for products based on fossil fuels has demonstrated the imperative need to develop new technologies capable of using renewable resources. In this context, the use of biomass to obtain chemical intermediates and fuels has emerged as an important area of research in recent years, since it is a renewable source of carbon in great abundance. It has the benefit of not contributing to the additional emission of greenhouse gases since the CO2 released during the energy conversion process is consumed by it through photosynthesis. In the presented review, the authors provide an update of the literature in the field of biomass transformation with the use of niobium-containing catalysts, emphasizing the versatility of niobium compounds for the conversion of different types of biomass.